Anterior Pelvic Ring Fracture Pattern Predicts Subsequent Displacement in Lateral Compression Sacral Fractures. Issue 11 (November 2022) - Ellis, Jonathan D.; Shah, Nihar S.; Archdeacon, Michael T.; Sagi, H. Claude
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objective: To determine if anterior pelvic fracture pattern in lateral compression (LC) sacral fractures correlates with subsequent displacement on examination under anesthesia (EUA) or follow-up in both nonoperative and operative cases. Design: Retrospective cohort study. Setting: Level 1 trauma center. Patients: Two hundred twenty-seven skeletally mature patients with traumatic LC (OTA/AO 61B1.1, 61B2.1-2, and 61B3.1-2) pelvic ring injuries treated nonoperatively, with EUA, or with pelvic fixation were included. Intervention: The study intervention included retrospective review of patients' charts and radiographs. Main Outcome Measurement: Displacement on EUA or follow-up radiographs (both operative and nonoperative) correlated with anterior pelvic ring fracture pattern. Results: Independent of sacral fracture pattern (complete or incomplete), risk of subsequent displacement on EUA or at follow-up after both nonoperative and operative treatments correlated strongly with ipsilateral superior and inferior pubic rami fractures that were either comminuted (95.6%, P < 0.001) or oblique (100%, P < 0.001). Patients with transverse or lack of inferior pubic ramus fracture did not displace (0%, P < 0.001). Out of 21 LC injuries treated with posterior-only fixation, displacement at follow-up occurred in all 11 patients (100%) with comminuted and/or oblique superior and inferior pubic rami fractures. Nakatani zone I and II rami fractures correlated most with risk of subsequent displacement. Conclusions: Unstable anterior fracture patterns are characterized as comminuted and/or oblique fractures of ipsilateral superior and inferior pubic rami. EUA should be strongly considered in these patients to disclose occult instability, for both complete and incomplete sacral fracture patterns. Additionally, these unstable anterior fracture patterns are poor candidates for posterior-only fixation and supplemental anterior fixation should be considered. Irrespective of sacral fracture pattern (complete or incomplete), nonoperative management is successful in patients with transverse or lack of inferior pubic ramus fractures. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.